Decimodrilus, a new enchytraeid genus from Korea (Annelida, Clitellata, Enchytraeidae) - Dózsa-Farkas, Klára; Nagy, Hajnalka; Felföldi, Tamás; Hong, Yong (Zootaxa, 2019)
Two new species of the new genus Decimodrilus gen. n. are described in this paper from oak forests of South Korea using a combination of classical morphology and DNA-based molecular taxonomy. A characteristic trait of the new genus is the occurrence of the intestinal diverticula in segments IX–X. The main morphological features of the new genus are: 4–5(6) straight chaetae per bundle, origin of dorsal vessel in clitellar region, anteseptale of nephridia consisting of funnel only, coelomocytes only mucocytes, oesophageal appendages absent, spermathecae united proximally and connected jointly with the oesophagus. Decimodrilus diverticulatus sp. n. has spermathecae with two diverticula-like protrusions and two globular sperm masses. D. globulatus sp. n. has spermathecae with two or three sperm rolls. Molecular taxonomic analysis based on a concatenated phylogenetic tree supports the status of the new genus and that of the two new species.